Could the proposed WTO Special Safeguard Mechanism protect farmers from low international prices?. (January 2015) - Thennakoon, Jayanthi; Anderson, Kym
Highlights: SSM benefits to producers in importing countries may be illusory. Illusion is greater the more exporting countries also seek to avert producer losses. Rice-exporting countries insulate around half as much as rice-importing countries. Similar insulation occurs when rice prices spike upwards, with opposite effects. Underscores need to strengthen WTO disciplines on farm export and import policies. Abstract: This paper offers an empirical analysis of the proposal by some developing countries for an agricultural Special Safeguard Mechanism (SSM) in the World Trade Organization. It draws on political economy and market theory to demonstrate that the loss-averting domestic producer benefits that proponents believe the SSM would offer agricultural-importing developing countries may be illusory, insofar as agricultural-exporting countries also seek to avert producer losses. By way of illustration, the paper then uses time series data to analyze past government responses to fluctuations in the world's rice markets. The results suggest that the proposed SSM would deliver at most only a small fraction of the loss-averting benefits that have been advertised by the proponents of the SSM. Since the analysis applies to upward as well as downward spikes in international prices, it underscores the importance of strengthening multilateral disciplines on both import and export trade interventions to reduce beggar-thy-neighbor unilateral trade policy responses to food price fluctuations.